FISIOMOTRICITY OF ADEQUATE INTENSITY THE PAIN THRESHOLDS: EFFECTIVENESS ON THE PIMÁX AND PEMÁX OF AGED WOMEN WITH OSTOPOROSIS. (Fiep Bulletin - online, 2013)
to compare the level of pain, Pimáx and Pemáx in aged womem with osteoporosis before and after the application of a fisiomotriz program. METHODOLOGY: sample consisting of 29 aged womem, between 65 and 70 years of age, sedentary, with pain and functional limitation, divided in two groups, in accordance with a diagnosis of pain of low intensity/ pain of high intensity. The variable had been pain, Pimáx and Pemáx. For the pain evaluation it was used analogical Escala visual e, manuvacuometro for the mensury of Pimáx and Pemáx. Later they had entered a fisiomotriz program, that used four gradual levels of exercises during 16 weeks. The data before and after-program had been studied through descriptive statistics and inferencial with index it has limited for acceptance/negation settled in ALPHA ± 0.05. An Analysis of Variance of Kruskal Wallis with its respective index was used independence Qui-square (c2). RESULTS: It was verified changes in the improvement of the pain of all the integrant ones with significant difference, having it as resulted, the Chi2 value = 0,0006, with 1 (gl), p< 0.05. In reference to the question Pimáx Pemáx in the group of lesser pain statistical was definite for PI, in Qui-Square test a “p” = 0, 1183 and for FOOT 0, 2276, both greater that 0, 05, no longer group of lesser pain statistical was definite for PI, in Qui-Square test a “p” = 0, 0161 and for FOOT 0, 0018, both minor who 0, 05. CONCLUSION: the analyzed fisiomotriz program revealed all effective in the improvement of pain in the amostral group, already the answers of Pimáx and Pemáx had been significant only in the group of lesser pain.